A new brown-winged Mysidia Westwood from the Guianas (Hemiptera: Derbidae) - Haas, Matthé Cornelis De; Bartlett, Charles R. (Zootaxa, 2026)
A new species of fully brown-winged Mysidia Westwood, 1840, M. undulata sp. nov. is described from material recently collected in French Guiana, additional specimens are recorded from Guyana and Suriname. The novel taxon is similar to M. inquinata Broomfield, 1985, but differs in details of the male genitalia.